BNC1 inhibits the development and progression of gastric cancer by regulating the CCL20/JAK-STAT axis - Lixin Liu; Li Xiong; Hong Peng; Qin Deng; Kang Liu; Shusen Xia (PeerJ)
The role of basonuclin 1 (BNC1), a zinc finger protein-specific transcription factor, in gastric cancer remains unclear. In this study, BNC1 was downregulated in gastric cancer and functioned as a tumor suppressor. Through integrative analyses of transcriptome sequencing and functional assays, C-C motif chemokine ligand 20 (CCL20) was identified as a direct downstream target of BNC1. Overexpression of BNC1 inhibited the proliferation, migration, and invasion of gastric cancer cells both in vitro and in vivo. Mechanistically, BNC1 suppresses CCL20 expression by binding to its promoter, leading to reduced activation of the JAK-STAT signaling pathway and promoting apoptosis in gastric cancer cells. These findings highlight the pivotal role of BNC1 in gastric cancer progression and suggest that targeting BNC1 and its downstream pathways could serve as a potential therapeutic strategy.